Implementasi Internet Of Things Buka Tutup Gorden Dan Lampu Otomatis - Muhamad Febryan; Roy Mubarak (CV. Multi Kreasi Media, 2022)
In human life, sunlight is very necessary as well as the condition of the night which is very necessary for rest time in the place of residence, namely the house. Inside the house there are curtains and lights where every human being in the morning will turn off the lights, open the curtains so that sunlight can enter the house. That way it becomes natural lighting, as well as at night people will generally turn on the lights as lighting around the house and close the curtains so that they can protect the privacy of the house and can also rest. However, we are often worried when the house is empty or when we travel for a long time, no one controls the curtains and lights in the morning and at night, and when the lights are left on continuously, of course it will waste electricity, be unsightly, and also invite someone's intentions. which is not good when you know the condition of the house is empty. The purpose of making this tool is to help residents of the house when they are sick or for elderly parents in controlling curtains and lights automatically using the LDR light sensor and can also use applications. In this research method using the IOT method using an LDR light sensor and a NodeMCU ESP8266 microcontroller.